THE DEFINITION AND LOCATION OF ALTRUISM AMONG PRO-SOCIAL BEHAVIORS - DÜZGÜNER, SEVDE (ILAHIYAT BILIMLERI ARASTIRMA VAKFI, 2019)
Investigating emotions, thoughts, and behaviors of human being, psychology studies pro-social behavior from various perspectives. Since altruism is related to sociality and morality it is discussed mostly in social psychology and psychology of religion. But recently, altruism has attracted attention in general psychology with the development of positive psychology. This has led to be published many studies on altruism in the literature. These studies include different approaches to definition and scope of altruism. Altruism, generally, defined as helping without expectation of personal benefit, takes an important place in the literature. Altruism is used synonymous with some concepts like helping, self-sacrifice, and isar (which is used in Turkish literature with the meaning of helping others even the person himself in need). Yet the determination of borders and locations of concepts is necessary to build psychological theory, research, and practice on firm basis. This paper presents information about pro-social behavior and definitions of altruism. Then it mentions nuances of other pro-social concepts in order to determine the location of altruism. It presents a concept map of altruism and definition chart for pro-social behaviors as well.
Keywords: Psychology of Religion; Pro-social Behavior; Helping Behavior; Altruism; Isar